High strain rate deformation of aged TRIP Ti-10V-2Fe-3Al (wt.%) examined by in-situ synchrotron X-ray diffraction. (15th February 2023) - Ellyson, B.; Saville, A.; Fezzaa, K.; Sun, T.; Parab, N.; Finfrock, C.; Rietema, C.J.; Smith, D.; Copley, J.; Johnson, C.; Becker, C.G.; Klemm-Toole, J.; et al.
Abstract: Transformation Induced Plasticity (TRIP) is a promising avenue for tailoring the work hardening response of metastable β titanium (Ti) alloys. Here we show that aged TRIP Ti-10V-2Fe-3Al (wt.%) maintains higher elongations and flow stresses as strain rate increases, if phase stability and microstructural characteristics are tuned. Low temperature aging influences the matrix β phase stability by ω phase precipitation, which affords a promising way to impact the TRIP effect and obtain desirable mechanical properties, ranging from high damping capacity to good strength/ductility combinations. Although TRIP is active during quasi-static and dynamic testing up to 2000 s −1, increasing aging time and/or strain rate reduces the overall propensity for the TRIP effect and extent of transformation, which occurs rapidly just at the onset of yielding. TRIP with ω phase precipitation provides interesting alloying, microstructure, and property design strategies for engineering applications like lightweight protective structures, where high strains and the need for energy absorption are encountered. Graphical abstract: